Effectiveness of Dayak (Eleutherine palmifollia (L) Merr) Extracts Against Escherichia coli In Vitro - Siti Mahmudah; Akhmad Muntaha; Ahmad Muhlisin (Tropical Health and Medical Research, 2019)
Dayak onion (Eleutherine palmifolia (L.) Merr) is hereditary used by the Indonesian Kalimantan Dayak community as a medicinal plant with antimicrobial activity. The active ingredient of Dayak onions can inhibit the growth of bacteria such as Escherichia coli. The purpose of this study was to determine the effectiveness of Dayak extract (Eleutherine palmifollia (L) Merr) in inhibiting the growth of Escherichia coli in vitro. This research method is experimental. Posttest Only Control Group Design research design. Research Results Show that Dayak onion extract can inhibit Escherichia coli with concentrations of 10% (6 mm), 20% (8 mm), and 30% (11 mm), 40% (13 mm), 50% (16 mm), 60 % (18 mm) and 70% (20 mm), 80% (20 mm), 90% (24 mm) and 100% (30 mm). The conclusion of the study of Dayak extract has a different effect on the growth of Escherichia coli with a significance value of 0,000